The contribution of civil society in legislative process - Chavan, Vijay A.; Salunke, Pratapsinh B. (2013)
The sovereign function of the Parliament is to make, amend or repeal the laws, where welfare of the people should be at focal point. In relation to the Parliament, the process of law making or the legislative process, may be defined as 'the process by which a legislative proposal brought before it, is transmitted into the law of the land'. In light of the Lokpal movement it can be said that the role of the civil society has become momentous in the legislative process. - Reproduced.
Keywords: Civil society